1994
DOI: 10.1073/pnas.91.9.3804
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effects of bombesin and epidermal growth factor on cancers.

Abstract: Bombesin and gastrin-rleas peptde act as autocrine mitogens in various cancers. Bombesin ataist RC-3095 inhibited growth in some cancers and slowed the progression of premalignant lesions, possibly by downregulating epidermal growth factor (EGF) receptors. Since the EGF receptor mitogen response Involves tyrosine kinase stimulation, we tested the hypotheses that bombesin stimulates, and RC-3095 inhibits, phosphorylation; EGF and bombesin promote the phosphorylation of the same substrates; and EGF and bombesin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 31 publications
(29 reference statements)
0
39
1
1
Order By: Relevance
“…In our model, EGF neither alone nor in combination with bombesin altered the growth of A375-6 cells. These findings are in contrast to other observations with various tumour cell lines: RC-3095, another specific bombesin receptor antagonist, inhibited growth and phosphorylation of growth-related peptides; furthermore, these effects were more pronounced in combination with EGF [23].…”
Section: Discussioncontrasting
confidence: 99%
“…In our model, EGF neither alone nor in combination with bombesin altered the growth of A375-6 cells. These findings are in contrast to other observations with various tumour cell lines: RC-3095, another specific bombesin receptor antagonist, inhibited growth and phosphorylation of growth-related peptides; furthermore, these effects were more pronounced in combination with EGF [23].…”
Section: Discussioncontrasting
confidence: 99%
“…In several in vivo tumor models (including SCLC and estrogen-dependent and estrogen-independent MTX mouse mammary cancers), treatment with a synthetic bombesin/GRP antagonist, RC-3095, resulted in the downregulation of EGFR mRNA expression levels (Pinski et al, 1994;Halmos and Schally, 1997;Szepeshazi et al, 1997;Koppan et al, 1998). Moreover, Liebow et al showed that bombesin and EGF seemed to promote phosphorylation of similar substrates (Liebow et al, 1994). Bombesin, which binds with high affinities to multiple BLP receptors, including NMBR and bombesin receptor subtype 4 (Akeson et al, 1997), has been shown to transactivate EGFR in the PC-1 prostate cancer cell line (Prenzel et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for these effects need to be clarified fully. Liebow et al (55) showed that BN-like peptides can up-regulate EGFRs in various cancers, and BN antagonists block this action. Consequently, BN͞GRP antagonists seem to inhibit MDA-MB-435 human estrogen-independent breast carcinoma by blocking the effects of BN-like peptides and inducing a down-regulation of the HER system.…”
Section: Discussionmentioning
confidence: 99%